Preparation of asymetric cellulose acetate membrane by phase inversion method of cellulose pulp from wood of sengon (Paraserianthes falcataria) - C. M. Rosnelly (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Cellulose acetate ultrafiltration membrane is one of kinds process of membrane which has been utilized in separation and purification processes. Cellulose acetate can be obtained from acetylation of cellulose sengon wood (Paraserianthes falcataria). Wood Sengon was used because it has potential as a raw material. There are three steps of cellulose diacetate manufacturing process: (1) activation of cellulose using acetic acid, (2) acetylation using acetic anhydride as reactant and sulfuric acid as catalyst, (3) hydrolysis. At each operating process was observed at 50oC. Preparation of cellulose diacetate membrane using phase inversion methode by addition of cellulose diacetate as polymer; N,N-Dimethyl formamide (DMF) as solvent, water as non-solvent, and Polyethylene glycol (PEG). Membrane pore size was determined by measuring Molecular Weight Cut Off (MWCO) using Dextran and Bovin Serum Albumine (BSA) as standard solution. Membrane morphology was observed by Scanning Electrone Microscope (SEM). Cellulose acetate of acetyl content of 39.66% and number average molecular weight 130,221 Da was obtained 30 minutes of activation time; one hour acetylation, and 15 hours hydrolysis. The addition of PEG produced a thickner layer and suppress the formation of macrovoid. SEM analysis shows a denser structure membrane morphology with better regularity of pore shape. The resulting membranes which were coagulated at lower temperature shows dense structure. High flux with low rejection obtained from the membrane with greater porosity and pore distribution. MWCO determination was based on the value of 80% rejection of dextran and BSA standard solution and the obtained pore size ranges obtained ≤ 67 kDa, and is still categorized as  ultrafiltration membrane